Cerebrovascular Disease and Its Associated Risk Factors - A Multifactorial Disease - Kaur, Jaspreet; Kaur, Jaswant; Gupta , Vishal; Mittal, Mridula (Current Overview on Disease and Health Research Vol. 6, 2022)
Cerebrovascular disease (CVD) is one of the leading causes of morbidity and mortality in adult life. Cerebrovascular diseases include stroke, transient ischemic attack (TIA), and vascular malformation. Ischemic strokes are the most common type of stroke and they account for 80%–85% of cerebrovascular diseases worldwide. Clinical presentation of stroke is variable depending upon the involvement of vascular territory. The etiology of ischemic stroke varies in different populations due to differences in lifestyle, environmental and genetic factors. It also varies across age groups. Hypertension, diabetes, dyslipidemia, and smoking have been identified as major risk factors. Many of the risk factors for stroke are modifiable. Recognition and early intervention of risk factors can help to reduce the incidence of ischemic stroke. The distribution of risk factors and their impact on ischemic stroke may vary by geographical area and cultural background. This chapter concentrated on the various risk factors that influence the development of CVD and its mechanism.